Resuscitative endovascular balloon occlusion of the aorta: an option for noncompressible torso hemorrhage?. Issue 2 (April 2019) - Kulla, Martin; Popp, Erik; Knapp, Jürgen
Abstract : Purpose of review: Hemorrhage is the major cause of early death in severely injured patients. In civilian emergency medical services, the majority of life-threatening bleedings are found in noncompressible body regions (e.g. abdomen and pelvis). Resuscitative endovascular balloon occlusion of the aorta (REBOA) has therefore been discussed in recent years as a possible lifesaving procedure and numerous studies, meta-analyses and guidelines have been published. In this review, the data situation of REBOA in the management of bleeding trauma patients is discussed and practical implementation is depicted. Recent findings: The typical indication for REBOA is a traumatic life-threatening hemorrhage below the diaphragm in patients unresponsive or only transiently responsive to the usual conservative therapeutic measures. REBOA appears to be a safe and effective procedure to reduce blood loss and stabilize the patient's hemodynamic status. However, surgical hemostasis has to be achieved within 30–60 min after occlusion of the aorta. Data on clear advantages of REBOA over resuscitative thoracostomy are inconclusive. Summary: REBOA could play an important role in the management of the severely bleeding patient in the future. Together with transfusion and therapy of coagulation disorders, REBOA may be an additional tool in the anesthetist's hands for trauma management in interprofessional care concepts.